Розробка оснащення для виготовлення деталі «Кронштейн» - Хало, Володимир Анатолійович; Khalo, Volodymyr (ЦНТУ, 2024)
Метою роботи є розробка оснащення для виготовлення деталі «Кронштейн». В роботі виконано розрахунок геометричних параметрів заготовки за переходами штампування; розрахунок розкрою металопрокату; розрахунок технологічних зусиль за операціями; розроблено конструкції оснащення для виготовлення деталі «Кронштейн»; виконано технічне нормування. Практичне значення: розроблено удосконалений технологічний процес виготовлення деталі «Кронштейн», розроблено конструкції оснащення для виготовлення деталі «Кронштейн», що дозволило знизити собівартість її виготовлення. The purpose of the work is the development of equipment for the manufacture of the "Bracket" part. In the work, the geometric parameters of the workpiece are calculated according to the stamping transitions; calculation of cutting of rolled metal; calculation of technological efforts by operations; developed equipment designs for the manufacture of the "Bracket" part; technical standardization has been carried out. Practical significance: an improved manufacturing process of the "Bracket" part was developed, equipment designs were developed for the production of the "Bracket" part, which made it possible to reduce the cost of its production.
Development of equipment for the manufacture of the "Bracket" part
Keywords: штамп; пуансон; матриця; пуансон-матриця; кронштейн; переходи штампування; технологічний процес; stamp; punch; matrix; punch-matrix; bracket; transitions of stamping; technological process